Profitability of mango marketing in different supply chains in selected areas of Chapai Nawabganj district (Bangladesh Journal of Agricultural Research, 2018)
A plenty of mangoes are spoiled and damaged every year due to improper postharvest handling and inefficient supply chain. Sufficient information are lacking on these issues in Bangladesh. The study assessed the postharvest handling of key actors in mango supply chains and estimated the post-harvest losses at different stakeholder level in Chapai Nawabganj district, Bangladesh. In total 83 respondents taking 30 mango growers and 53 mango traders were interviewed from Chapai Nawabganj and Dhaka districts. The study identified eight marketing channels for mango marketing. The prominent channel was Grower> Bepari> Urban Arathdar> Urban retailer> urban Consumer since 85.1% mangos moved through this channel. Bepari incurred the highest marketing cost (Tk.7338/ton) due to long distance coverage followed by retailer (Tk.1218/ton) and Faria (Tk.738/ton). Faria received the highest net margin (Tk.8068/ton) due to lower marketing cost and spoilage followed by retailer (Tk. 6601/ton) and Bepari (Tk.5394/ton).The results revealed that the estimated average postharvest losses were 14.11% and 9.61% at farm and traders’ level respectively. At farm level, these losses occurred during harvesting, sorting & grading, and transportation. Harvesting losses were due to cracking, bruising, compression, and disease and insect infestation. The highest loss was recorded at retail level (4.64%) followed by Bepari (3.95%). Farmers and Farias used different local carriers, whereas trucks and pick up van were used by Bepari to transport mango from assemble markets to urban wholesale markets. Major marketing problems in the supply chain were delayed sale and lack of buyers.Bangladesh J. Agril. Res. 43(3): 471-487, September 2018